Physiological basis and practice of rehabilitation medicine in the management of individuals with spinal cord injury. (January 2017) - Tajima, Fumihiro; Kamijo, Yoshi‐ichiro; Sumiya, Tadashi; Nishimura, Yukihide; Arakawa, Hideki; Nakamura, Takeshi; Furusawa, Kazunari
Abstract: Rehabilitation medicine has made dramatic and successful progress in recent years, and neurologists and physiatrists have faced greater challenges in coordinating the clinical management of patients with spinal cord injuries (SCI). To ensure the best clinical outcome in SCI, physiatrist need to comprehend the dysfunctions of various body systems and the physiological aspects of the central nervous, musculoskeletal and autonomic nervous system, as well as the social support system. Furthermore, the rehabilitation team, including physiatrists, nurses, physical therapists, social workers and peer supporters, should provide surgical treatment, clinical management, drug therapy and optimal assistance for SCI. We believe that the first important task in the management of SCI patients is precise diagnosis of the site of the spinal cord lesion. This should be followed as soon as possible by spinal surgery to stabilize the vertebral column. The day after surgery, the patient should be handled by the rehabilitation team. Orthostatic loads should be applied, and exercise of the remaining muscles should begin in order to ensure early mobilization and satisfactory repair. Our group has carried out extensive research into the pathophysiology of the cardiovascular, respiratory, endocrine and autonomic nervous systems and exercise responses in SCI, and reported the benefits and improvements of early mobilization and exercise, and the safety of physical medicine and rehabilitation. The rehabilitation team should follow these individuals closely to provide long‐term clinical care, and deal with social issues arising during the chronic phase. Participation in sports activities (para‐sports) could work well to improve the physical condition of these individuals.